Aklanon Composo as literary text . - Viloria, Janice M.
One of the surviving cultural practices in Aklan today is the Aklanon composo. The composo is not popular nowadays and seldom heard, but then a few people still continue to sing them. These songs are simple and since they are called 'folk' they are usually considered less 'poetic' (in a Western sense). then again, in spite of their simplicity adn their being less popular, still they may be considered literary. These songs also have a rhyming pattern and meter. Possessing appropriate symbols, metaphors and images, it is likely possible that these songs really deserve to be studied and be called literary.